Water footprint assessment and its importance in Indian context: a meta-review - Mukesh Kumar Mehla; Mahesh Kothari; Pardeep Kumar Singh; Sita Ram Bhakar; Kamal Kishore Yadav (Water Supply, 2023)
With the increasing population and per capita demand for freshwater, the burden of natural resources has increased many folds. Indian agriculture is still largely dependent on conventional methods of crop production that are mainly inefficient. Water security is essential for social and economic development, having an indispensable role in enhancing health, well-being, and economic progress, particularly in a developing country like India. Water footprint (WF) is an important indicator that helps ascertain the direct and indirect use of water in any process. WF modeling in agriculture enables us to pinpoint the impacts and limitations of the current crop production system. Assessing vulnerabilities across various regions and time helps us prepare actions to improve water productivity and promote sustainable water use. There is considerable spatial variability in blue, green, and gray WF among the different states of India due to their varied climate, soil, and topographic characteristics. WF assessment is critical for developing water allocation strategies, planning water trade, making policies, and implementing remedial measures. This paper describes the significance of WF and its proper management for sustainable crop production in India. HIGHLIGHTS Water security is essential for social and economic development, especially for countries like India, supporting nearly 17.1% of the world's population.; The average annual per capita water availability has declined over the years while demand from various sectors mounted over the years.; Among the various countries of the world, India has the largest total WF at 1047 billion cubic meters per year (BCM/year), followed by China (967 BCM/year) and the USA (826 BCM/year).;